Pengembangan Model Crowdfunding Syariah Untuk Pembiayaan UMKM (Studi Pada Platform Fintech Ethis) - Maharani, Rizka Dwi; Halimah, Rohana Nur; Anani, Silfiya Maulida; Lutfi, Sofia Nur Azizah (Social Science Academic, 2023)
The purpose of this study is to determine the development of fintech in Indonesia through the ethical platform using musyarakah contract financing and wakalah contracts. In dealing with problems in this financing can be done by providing several alternative strategies to the problems that occur in the funding that occurs. The type of research used is qualitative research with descriptive methods. The data source obtained from this research is secondary, which is obtained from observations through the Ethis website. Analysis of the data obtained comes from using data reports on the development of fintech in Indonesia. The results of the study show developments from year to year which can be seen from the public's interest in using funding in fintech. This means that there is progress in the use of funding on the ethical platform, therefore public interest in its use is increasing. With the emergence of this can increase public interest and interest in funding in the platform.